Establishing integrated rural–urban cohorts to assess air pollution-related health effects in pregnant women, children and adults in Southern India: an overview of objectives, design and methods in the Tamil Nadu Air Pollution and Health Effects (TAPHE) study. Issue 6 (10th June 2015) - Balakrishnan, Kalpana; Sambandam, Sankar; Ramaswamy, Padmavathi; Ghosh, Santu; Venkatesan, Vettriselvi; Thangavel, Gurusamy; Mukhopadhyay, Krishnendu; Johnson, Priscilla; Paul, Solomon; Puttaswamy, Naveen; Dhaliwal, Rupinder S; Shukla, D K; et al.
Abstract : Introduction: In rapidly developing countries such as India, the ubiquity of air pollution sources in urban and rural communities often results in ambient and household exposures significantly in excess of health-based air quality guidelines. Few efforts, however, have been directed at establishing quantitative exposure–response relationships in such settings. We describe study protocols for The Tamil Nadu Air Pollution and Health Effects (TAPHE) study, which aims to examine the association between fine particulate matter (PM2.5 ) exposures and select maternal, child and adult health outcomes in integrated rural–urban cohorts. Methods and analyses: The TAPHE study is organised into five component studies with participants drawn from a pregnant mother–child cohort and an adult cohort (n=1200 participants in each cohort). Exposures are assessed through serial measurements of 24–48 h PM2.5 area concentrations in household microenvironments together with ambient measurements and time-activity recalls, allowing exposure reconstructions. Generalised additive models will be developed to examine the association between PM2.5 exposures, maternal (birth weight), child (acute respiratory infections) and adult (chronic respiratory symptoms and lung function) health outcomes while adjusting for multiple covariates. In addition, exposure models are being developed to predict PM2.5 exposures in relation to household and community level variables as well as to explore inter-relationships between household concentrations of PM2.5 and air toxics. Finally, a bio-repository of peripheral and cord blood samples is being created to explore the role of gene–environment interactions in follow-up studies. Ethics and dissemination: The study protocols have been approved by the Institutional Ethics Committee of Sri Ramachandra University, the host institution for the investigators in this study. Study results will be widely disseminated through peer-reviewed publications and scientific presentations. In addition, policy-relevant recommendations are also being planned to inform ongoing national air quality action plans concerning ambient and household air pollution.